(untitled) (Tzintzun, Revista de Estudios Históricos, 2020)
This article investigates the construction of Mexican imaginaries about the United States, focuses on the representations and opinions generated in the newspaper El Diario del Hogar, arguing that American interventionism in Central America and tensions on the northern border detonated rising nationalism and anti-Americanism. The time centerpiece of this study is 1910 by virtue of the reason that this was a year where American aggressions converged in Central America, with the presence of opponents of the Diaz regime on the northern border and the lynching of a Mexican immigrant in Texas. In order to reconstruct this amalgam of anti-American and anti-porfirist discontent, the text argues, that these three factors detonated unfavourable lines of opinion with respect to the northern neighbor, in a context where the Fourth Pan American Conference and the Celebration of the Centenary of The Independence of Mexico took place. The analysis will be conducted through an anti-government newspaper, complemented by the diplomatic correspondence of Ambassador Henry Lane Wilson, as well as other documents from the Library of Congress in Washington, in order to obtain a triangular view of the issue.